Intracranial Hemorrhage Caused by Vitamin K Deficiency Beyond Neonatal Period - Adhikari, Sudhir; Gauchan, Eva; Malla, Tejesh; Sathian, Brijesh; Rao, Kalipatanam Seshagiri (Journal of Nepal Paediatric Society, 2017)
Vitamin K deficiency bleeding (VKDB) can manifest as intracranial hemorrhage (ICH) and is still prevalent in poor resource countries. Infants aged one to twelve months with the diagnosis of ICH from 1st July 2011 to 30th June 2016 were included. There were 16 cases of ICH attributed to vitamin K deficiency. Clinical presentations were anemia16 (100%), bulged fontanel 13(81.3%), seizures 10(62.5%), vomiting 8(50%) and fever 9(56.3%). Mean INR at admission was 8.575±7.267 and 1.868±0.838 after three doses of vitamin K administration. Sites of intracranial bleed were parenchymal 5(31.3%), subdural 4(25%), extradural 2(12.5%), ventricular 2(12.5%). In 3(18.8%) of cases bleeding was more extensive involving more than one site. Mortality was 4(25%) and 3(18.8%) had abnormal neurological findings at discharge. There is an urgent need for national policy for vitamin K prophylaxis at birth.